Exploration of The Didactic Situation of Linear Equations in SMP Suci Murni Medan - Nilam Sari (Universitas Wiralodra, 2023)
One way to design good learning is to pay attention to the possibility of the learning flow that will occur in the classroom and the possible processes that students will go through, then make up what the teacher should do when this happens. These possibilities are also called the hypothetical learning trajectory. In this study focused on the design of mathematics learning on the material system of two-variable linear equations in grade VIII junior high school involving one class of 18 people. The instruments used were tests and non-tests. This study aims to explore pedagogical phenomena to formulate alternative learning designs for linear equations through problem-based learning. Perspectives and pedagogical encouragement about teaching mathematics during the learning process are reflected in the deepest thoughts and emotions of students and teachers. The research method uses a qualitative type of didactical design research, which is a type of learning design research where learning designs can be formulated from several perspectives, namely the theory of learning trajectories and their obstacles and learning situations during the learning process. The stages carried out in this research are: 1) introduction and analysis of the problem; 2) analysing the curriculum related to the mathematics textbooks used; 3) Identify the characteristics of learning obstacles and learning barriers; 4) identify didactic situations during learning.The results of the research yielded the characteristics of learning trajectories and learning obstacles, which were used as the basis for the pedagogical situation of learning linear equation material through exploratory problem-based learning.